2016
DOI: 10.5435/jaaos-d-15-00181
|View full text |Cite
|
Sign up to set email alerts
|

The Morel-Lavallée Lesion: Diagnosis and Management

Abstract: The Morel-Lavallée lesion is a closed soft-tissue degloving injury commonly associated with high-energy trauma. The thigh, hip, and pelvic region are the most commonly affected locations. Timely identification and management of a Morel-Lavallée lesion is crucial because distracting injuries in the polytraumatized patient can result in a missed or delayed diagnosis. Bacterial colonization of these closed soft-tissue injuries has resulted in their association with high rates of perioperative infection. Recently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
139
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(147 citation statements)
references
References 16 publications
1
139
0
7
Order By: Relevance
“…reported that the definitive MLL treatment is guided by the size, location, and age of the lesion. [ 35 ] However, there is no universally accepted treatment algorithm for MLL and still the diagnosis and management based on the treating surgeon knowledge, imaging characteristics, and treatment availability. [ 25 ]…”
Section: Discussionmentioning
confidence: 99%
“…reported that the definitive MLL treatment is guided by the size, location, and age of the lesion. [ 35 ] However, there is no universally accepted treatment algorithm for MLL and still the diagnosis and management based on the treating surgeon knowledge, imaging characteristics, and treatment availability. [ 25 ]…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the space allows the accumulation of blood, necrotic fat, lymphatic fluid, and other inflammatory mediators. These types of lesions/accumulations have been described following high-energy trauma, such as motor vehicle incidents, assaults, sport-related injuries [ 1 , 2 ], and surgical procedures, such as abdominoplasty, with [ 3 , 4 ] and without [ 5 ] liposuction.…”
Section: Discussionmentioning
confidence: 99%
“…Other case series have similarly demonstrated higher predilection for lower extremity involvement with 60% [ 9 ] up to 81% [ 10 ]. If MLL remains untreated, a prolonged inflammatory process may ensue instigating formation of a pseudocyst leaving potential for infection and necrosis [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations